HIF-1Î± mediates visfatin-induced CTGF expression in vascular endothelial cells - Wu, W.; Li, J.; Zhao, M.; Liu, X. (Cellular and Molecular Biology, 2017)
Visfatin is an adipokine that functions as a mediator of endothelial dysfunction and cardiovascular diseases. Connective tissue growth factor (CTGF) is a key factor in vascular remodeling and atherosclerosis. However, the association between visfatin and CTGF is unclear. Therefore the study was to test the hypothesis that visfatin could modulate the expression of CTGF in vascular endothelial cells. In our study, cultured endothelial cell line EA.Hy926 cells were treated with different concentrations of visfatin for different times. The CTGF gene expression was analyzed by real-time PCR, and the protein expression of CTGF was assessed by Western Blot. The results showed that 100ng/mL concentration of visfatin could induce CTGF mRNA expression after 6 hours treatment, which peaked at 24 hours. And 100ng/mL concentration of visfatin also increased CTGF protein production after 12 hours treatment in EA.Hy926 cells. The expression of transforming growth factor-Î²1 (TGF-Î²1) mRNA was almost unaffected in cells treated with visfatin, whereas the expression of hypoxia inducible factor-1Î± (HIF-1Î±) was increased significantly. Moreover, knockdown of HIF-1Î± by its specific shRNA inhibits the effect of visfatin on CTGF expression. In conclusion, the up-regulation of CTGF expression by visfatin might be mediated via HIF-1Î± -dependent pathway, but not the TGF-Î²1 pathway in EA.Hy926 cells.